A pharmacovigilance study of chronic kidney disease in diabetes mellitus patients with statin treatment by using the US Food and Drug Administration adverse event reporting system - Zhang, Jingyi; Guo, Yuting; Wei, Chunyan; Yan, Yu; Shan, Huifang; Wu, Bin; Wu, Fengbo (Frontiers in Pharmacology, 2024)
Background: Statins were regarded as a main medication for managing hypercholesterolemia. Administration of statin therapy could reduce the incidence of cardiovascular disease in individuals diagnosed with type 2 diabetes mellitus (DM), which was recognized by multipal clinical guidlines. But previous studies had conflicting results on whether the long-term use of statins could benefit the renal function in diabetic patients Aim: To evaluate the association between statin treatment and Chronic Kidney Disease in DM patients. Methods:This is a retrospective disproportionality analysis and cohort study based on real-world data. All DM cases reported in US Food and Drug Administration adverse event reporting system(FAERS) between the first quarter of 2004 and the fourth quarter of 2022 were included. Disproportionality analyses were conducted by estimating the reporting odds ratio (ROR) and the information component (IC).We further compared the CKD odds ratio (OR) between the statins group and the other primary suspected drug group among the included diabetes mellitus cases. Results: We finally included 593647 DM cases from FAERS, 5113 (5.31%) CKD cases in the statins group and 8810 (1.77%) CKD cases in the control group. Data analysis showed that the statins group showed a significant